Ciliary neurotrophic factor promotes motor reinnervation of the musculocutaneous nerve in an experimental model of end-to-side neurorrhaphy - Dubový, Petr; Raška, Otakar; Klusáková, Ilona; Stejskal, Lubomír; Celakovský, Pavel; Haninec, Pavel (BMC neuroscience, 2011)
BACKGROUND: It is difficult to repair nerve if proximal stump is unavailable or autogenous nerve grafts are insufficient for reconstructing extensive nerve damage. Therefore, alternative methods have been developed, including lateral anastomosis based on axons' ability to send out collateral sprouts into denervated nerve. The different capacity of a sensory or motor axon to send a sprout is controversial and may be controlled by cytokines and/or neurotrophic factors like ciliary neurotrophic factor (CNTF). The aim of the present study was to quantitatively assess collateral sprouts sent out by intact motor and sensory axons in the end-to-side neurorrhaphy model following intrathecal administration of CNTF in comparison with phosphate buffered saline (vehiculum) and Cerebrolysin. The distal stump of rat transected musculocutaneous nerve (MCN) was attached in an end-to-side fashion with ulnar nerve. CNTF, Cerebrolysin and vehiculum were administered intrathecally for 2 weeks, and all animals were allowed to survive for 2 months from operation. Numbers of spinal motor and dorsal root ganglia neurons were estimated following their retrograde labeling by Fluoro-Ruby and Fluoro-Emerald applied to ulnar and musculocutaneous nerve, respectively. Reinnervation of biceps brachii muscles was assessed by electromyography, behavioral test, and diameter and myelin sheath thickness of regenerated axons. RESULTS: Vehiculum or Cerebrolysin administration resulted in significantly higher numbers of myelinated axons regenerated into the MCN stumps compared with CNTF treatment. By contrast, the mean diameter of the myelinated axons and their myelin sheath thickness in the cases of Cerebrolysin- or CNTF-treated animals were larger than were those for rats treated with vehiculum. CNTF treatment significantly increased the percentage of motoneurons contributing to reinnervation of the MCN stumps (to 17.1%) when compared with vehiculum or Cerebrolysin treatments (at 9.9 or 9.6%, respectively). Reduced numbers of myelinated axons and simultaneously increased numbers of motoneurons contributing to reinnervation of the MCN improved functional reinnervation of the biceps brachii muscle after CNTF treatment. CONCLUSION: The present experimental study confirms end-to-side neurorrhaphy as an alternative method for reconstructing severed peripheral nerves. CNTF promotes motor reinnervation of the MCN stump after its end-to-side neurorrhaphy with ulnar nerve and improves functional recovery of the biceps brachii muscle.
Keywords: Animals; Motor Neurons; Female; Musculocutaneous Nerve; Rats, Wistar; axony; ženské pohlaví; ciliární neurotrofický faktor; Peripheral Nerve Injuries; poranění periferního nervu; regenerace nervu; Nerve Regeneration; Nerve Transfer; nervus musculocutaneus; motorické neurony; krysa rodu Rattus; nervový transfer; Ciliary Neurotrophic Factor; zvířata; Rats; potkani Wistar; Axons